Success and Development of Older Workers as a Challenge to Higher Education - I. B. Durakova; E. V. Mayer (Высшее образование в России)
The article implements an attempt to present the success of older workers in the conditions of the sporting paradigm and the formation of eco-thinking in organizations. The reasons for rethinking the prolonged working capacity of age workers as a “new normal” are shown. The article dwells on the features of teaching employment in higher education and makes the case for forming environmental conditions in universities to retain key professors and associate professors so that they can continue their creative work. The authors give characteristics of successful, healthy, active and productive ageing and suggest the measures that help to slow down the premature ageing of personnel.